Konsep Desain Taman Makam Umat Kristiani Mumbul Kabupaten Badung Bali - Fitri, Anisa; Kohdrata, Naniek; Sugianthara, Anak Agung Gede (Jurnal Arsitektur Lansekap; Vol.7, No.2, Oktober 2021DO - 10.24843/JAL.2021.v07.i02.p05, 2021)
Conceptual Design of Mumbul Christian Cemetery Badung Regency, Bali. Mumbul Christian Park has a land area of 1.6 ha and is located in a residential area. This study aims to identify the characteristics of the Mumbul Christian Cemetery, analyze and synthesize the potential and constraints on the site. This study used a survey method with data collection techniques through observation, interviews, and literature study. This study uses the Simonds (1996) design process stage method. The design process is divided into four stages, namely: Research, Analysis, Syntesis, and Design Plan. The division of space zones on the site is based on a concept that is in accordance with the meaning of death in Christianity, namely the zone of birth, the zone of temporary life and the zone of eternal life. The concept of Paradise of Memorial Park is the concept of a park as a garden of memories as well as a public space. The results of this research design can be used as a reference for thought and consideration in designing the landscape site and in other tomb garden areas.